Self-esteem and social skills in adolescents from San Miguelito- Píllaro Ecuador - Barreros-Guanin, Roxana (2024)
The objective of this research was to determine the relationship between self-esteem and social skills in adolescents from San Miguelito-Píllaro, Ecuador. The research has a non-experimental and quantitative design with a correlational scope and cross-sectional approach. Evaluation instruments included the Rosenberg self-esteem scale and the Goldstein social skills scale. A total of 220 adolescents participated, 55% (121) females and 45% (99) males aged 15 to 18. The findings indicate that levels of self-esteem are generally high, while social skills levels are mainly medium and high. Regarding gender based analysis, no significant differences were found in either variable. Furthermore, a significant positive correlation was observed between self-esteem and social skills levels, as well as between self-esteem and different types of social skills. It has been proven that higher levels of self-esteem are associated with higher levels of social skills, and vice versa.